Karakteristik Morfologi dari Formulasi Pupuk NPK Coated dengan Enkapsulasi Starch-PVA-Glycerol - Habibi, Wildan; Purnomo, Chandra Wahyu; Perdana, Indra (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
In modern agriculture, the application of NPK fertilizer plays an important role in food security. However, most commercial uncoated fertilizers have low nutrient absorption efficiency with 30-70% nutrient loss, advances to financial losses for farmers and causing environmental issues. Slow-release fertilizer (SRF) is the best solution to decrease loss rate, supplying nutrients sustainably, and reduces potential negative environmental effects. These fertilizers are made by physically encapsulating NPK fertilizer with organic hydrophobic materials (starch-polyvinyl alcohol (PVA)-glycerol). Double layered encapsulation is formulated by in-situ copolymerization of starch with vinyl acetate monomer from PVA in different ratios. Glycerol is added to increase the film compatibility. Scanning Electron Microscope (SEM) followed by Energy Dispersive X-ray (EDX) analysis reveals the morphological characteristic of uncoated and coated NPK samples. The surface micrograph of uncoated NPK exhibits fine spire crystals that are intensely cemented on to the surface with some bigger crystals of potassium chloride. The gaps and pores are also visible. The SEM micrographs of coated NPK depict layering and agglomeration that is a clear indication of the coating. A higher ratio of PVA increases agglomeration on the surface of coated NPK, representing dense and complete coverage with less pores and cavities occurs